Enabling enterprise risk management maturity in public sector organizations. Issue 6 (18th August 2022) - Mahama, Habib; Elbashir, Mohamed; Sutton, Steve; Arnold, Vicky
IMPACT: This article addresses an important public sector management issue—what and how organizational capabilities can be mobilized for effective deployment of enterprise risk management (ERM) in public sector organizations. The authors present a framework providing insights to public sector managers for enhancing risk management practices ABSTRACT Public sector reforms have led to risk management gaining prominence as a means for effective service delivery and a tool for accountability. The public sector has seen regulatory changes intended to empower managers to engage in appropriate risk management practices. The authors present a framework for effective enterprise-level risk management in public sector organizations. The framework includes three essential enablers of risk management and provides conceptualizations for guiding future empirical research.